Designing and implementing an urban river remediation. Issue 4 (11th September 2019) - Boom, Tom; Ellis, Mike; Richard, Don
Abstract: In 2017, Consumers Energy completed a sediment response action in the Flint River to address manufactured gas plant‐related impacts in sediments and at the groundwater‐surface water interface. The project site is located in an urban, channelized, developed reach of the river. Multiple property owners and site constraints presented unique challenges for the remedial design, including the presence of Hamilton Dam at the downstream edge of the site which was considered a high‐hazard dam in "very poor condition." An additional consideration was the City of Flint water crisis which was initially exposed in 2014. The sediment response action was not related to the water crisis because the site is located approximately two miles downstream of the City's water intake, but design, permitting, and construction began after 2014, so the timing added a heightened sense of awareness from the public stakeholders. The successful completion of the sediment response action was the result of deliberate planning, iterative engineering, and open communication with stakeholders that enabled a careful balancing of objectives with sometimes competing interests.